A decision tree–based classifier for E-visit service provision. (2nd July 2020) - Chern, Ching-Chin; Ho, Pin-Syuan; Hsiao, Bo
ABSTRACT: This study proposes a decision tree-based e-visit classification approach (DTEVCA) to determine clinic visits qualified as e-visits using clinics' medical records and patients' demographic data. This study assumes that health care insurance will subsidise e-visit service costs, in which case, identifying patients who benefit most from e-visit service is essential. Using a large data set from Taiwan's National Health Insurance, this study verifies the efficiency and validity of the DTEVCA. Results indicate that this approach can accurately classify in-office clinic visits that could switch to e-visit services. The straightforward rules of this decision tree also give insurance agencies a clear guideline to understand the circumstances of using e-visits and predict the effects of implementing e-visits in Taiwan. Result of this study can help countries improve the policy formulation process for physicians' use, or for academic research. The DTEVCA can update classification rules using new data to correct biases and ensure the stability of the e-visit system. In addition, the concept of this approach is feasible not only for e-visit service but also for other 'new services' such as new products or new policies.